Far beyond the garden gate : Alexandra David-Neel's journey to Lhasa - Brown, Don, 1949- (Houghton Mifflin Co., 2002)
Describes the life and travels of Alexandra David-Neel, who became a scholar of Buddhism and Tibet in the early twentieth century and trekked thousands of miles to reach Llasa, the Tibetan capital.